The Lived Experience of Caring for an Australian Military Veteran With Posttraumatic Stress Disorder. (October 2016) - Waddell, Elaine; Pulvirenti, Mariastella; Lawn, Sharon
There is limited literature on the experience of caring for an intimate partner with a mental health condition. Posttraumatic stress disorder (PTSD) is a common mental health condition for military veterans; yet, little is known about how partners experience and cope with these caring relationships. Using an interpretive phenomenological approach, we collected data through individual interviews with 20 female partners of male veterans diagnosed with PTSD living in South Australia. We found the emotional features of caring to be directly derived from the strength of commitment these carers had to their relationships. We show that lack of understanding of carers' lives, particularly by health providers and government, has resulted in a sense of social disconnect and invisibility that has contributed to stress and is a barrier to coping. Of vital importance to these carers was that partners of younger veterans should not have to suffer the same experiences.